Atenção à saúde dos usuários de álcool e outras drogas na concepção dos profissionais - Teixeira, Joze Karlem da Silva (2016)
Drugs have always accompanied humanity, but with the passage of time, the use of these substances passed from ritualistic scope for the search for pleasure. The drug was seen as a major problem and becomes researched in order to understand the problem and the model of health care to be followed. In this direction, the objectives are: learn the concepts of health professionals who care for drug users of CAPS Ad in a city in the interior of Rio Grande do Sul State, on health care in this space; analyze the elements that influence the conceptions of health professionals in relation to health care of drug users in CAPS Ad; and identify the knowledge of health professionals on public Politics related to the use of alcohol and other drugs current in Brazil. Data collection occurred from March to June 2015 through semi-structured interview developed individually and recorded, with 15 health professionals who are municipal employees and the Multidisciplinary Residency in Health. The interviews were transcribed and analyzed by thematic analysis. From Analysis three categories emerged: Conceptions of health professionals in relation to health care of drug users in Caps Ad; Elements that influence the conceptions of health professionals in relation to health care of drug users; Issues that tire and frustrate health professionals in relation to users. The ethical aspects of research involving human beings were respected, according to Resolution No. 466 of 2012 of the National Health Council. The results showed that some health professionals work guided by the logic of withdrawal, while others are more concerned with harm reduction. They understand the place that the drug plays in the life of the users and that permeates across by social issues. Also, they understand that public policy would be if they were resolving how they aim to be. The professionals expressed as complicating factors of the health care process, the lack of financial investment in services, lack of professionals and the sickness of the same; discontinuity at work due to professional exchanges, municipal health secretaries and coordinators; and crave a greater commitment on the part of health management. It concludes by emphasizing the importance of promoting dialogue between the different groups of health.